The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1980
DOI: 10.1136/vr.107.10.226
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic efficiency of ivermectin against naturally acquired bovine gastrointestinal nematodes

Abstract: Ivermectin, one of the new avermectin group of anthelmintics, was more than 99 per cent effective in removing all stages of Ostertagia ostertagi including inhibited larvae, and adult Trichostrongylus axei when administered to cattle orally at 100 microgram/kg body-weight or subcutaneously at 100 and 200 microgram/kg body-weight. High efficacy (> 98.6 per cent) was also obtained against adults and inhibited larvae of Cooperia oncophora at 100 microgram/kg orally or 200 microgram/kg by subcutaneous injection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Nematodes. Ivermectin is active against essentially all of the gastrointestinal nematode species that are generally regarded as being of pathogenic or economic importance in cattle; and, except in the case of one species (below), a high degree of efficacy is achieved with the standard dosage (Armour et al, 1980;Benz & Ernst, 1981a, b;Egertonet al, 1981b;Yazwinski et al, 1981b;Lyons et al, 1981b;Elliott & Julian, 1981).The drug is also effective against the extraintestinal nematodes Dicty ocaulus viviparus (Benz & Emst, 1981b;Egerton et al, 1981b;Lyons et al, 1981b) and Parafilaria bovicola (Swan e t al., 1983) those species in which tests have been made against inhibited or hypobiotic fourth-stage larvae, or against strains resistant to other anthelmintics, ivermectin has consistently been highly effective against such stages and strains. The drug is about equally effective against nematodes when given orally or parenterally.…”
Section: Cattlementioning
confidence: 99%
“…Nematodes. Ivermectin is active against essentially all of the gastrointestinal nematode species that are generally regarded as being of pathogenic or economic importance in cattle; and, except in the case of one species (below), a high degree of efficacy is achieved with the standard dosage (Armour et al, 1980;Benz & Ernst, 1981a, b;Egertonet al, 1981b;Yazwinski et al, 1981b;Lyons et al, 1981b;Elliott & Julian, 1981).The drug is also effective against the extraintestinal nematodes Dicty ocaulus viviparus (Benz & Emst, 1981b;Egerton et al, 1981b;Lyons et al, 1981b) and Parafilaria bovicola (Swan e t al., 1983) those species in which tests have been made against inhibited or hypobiotic fourth-stage larvae, or against strains resistant to other anthelmintics, ivermectin has consistently been highly effective against such stages and strains. The drug is about equally effective against nematodes when given orally or parenterally.…”
Section: Cattlementioning
confidence: 99%
“…The overall terapeutic dose in cattle and sheep is found to be 200 meg Ivermectin/kg bodyweight subcutaneously injected (Armour et. al.…”
Section: Tested Drugsmentioning
confidence: 99%
“…1 The avermectins are widely used as an anthelmintic for cattle in Brazil and around the world because of its high efficacy against a broad spectrum of nematode parasites and certain ectoparasites. Several studies have reported the efficacy of ivermectin 2,3,4,5 , doramectin 6,7,8,9,10 and abamectin 11,12,13,14 against the most important cattle gastrointestinal nematodes, the efficacy against adult Cooperia punctata of 95% is demonstrated.…”
Section: Identification Of Ivermectin and Doramectin-resistant Coopermentioning
confidence: 99%